Design of a 28 GHz Bandpass Filter for 5G Applications - Muhammad Rendra Perdana Kusuma Djaka; Gunawan Wibisono (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2023)
One of the essential passive devices is the Bandpass Filter. Since the frequencies used for this technology are diverse and each frequency has different characteristics that can affect signal quality, the Bandpass Filter is employed to filter the signals received by the antenna, ensuring that only the desired frequency signals are processed. Within the mm Wave range, 26 GHz and 28 GHz emerge as the two most relevant bands. Therefore, this paper presents the design of a schematic for a Bandpass Filter operating at mm-wave frequency (28 GHz) using Lumped-Distributed Parameters. The schematic is created using system design software, employing a standard normalized 5-pole/5th order prototyped Lowpass Chebyshev combined with a standard formalized 3-pole/3rd order prototyped Lowpass Chebyshev to control the desired bandwidth according to the design parameters. The designed Bandpass Filter at 28 GHz exhibits a Return Loss value of -281.579 dB, an Insertion Loss of -1.929E-15 dB, and a desired Bandwidth of 1 GHz